Friction Effect on Hydraulic Jump - Foroughi, Daniel (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
A theoretical relationship for calculating the sequent depth ratio of the hydraulic jump formed in rectangular horizontal and roughened bed channels has been offered. This has been achieved based on considering the effect of drag force due to bed roughness in the momentum equation of hydraulic jumps. Two dimensionless parameters, dimensionless drag effect and dimensionless roughness effect are developed in order to observe the effect of roughness height on the magnitude of drag. Also, the effect of dimensionless drag effect on drag coefficient during hydraulic jump is achieved for different roughness heights at the bottom of channel. Within this study, another important physical phenomena occurring during hydraulic jumps that is the roller length as well investigated. A new model is developed for estimating the roller length in rectangular channels in terms of conjugate depths and upstream flow velocity. The developed equation has been tested for different type of rectangular cross section roughened beds as well. Keywords: Hydraulic jump, roughened bed, rectangular channel, drag force, roller length.

ÖZ : Dikdörtgen kesitlerde taban pürüzlülüklerinin hidrolik sıçrama üzerinde yaptığı etki araştırılmış ve sıçrama öncesi ve sonrası su derinlikleri ile ilgili bağıntısı tanımlanmaya çalışılmıştır. Bağıntının elde edilmesinde hidrolik sıçrama anında momentumun korunumu ilkesi baz alınmış ve momentumun korunumu denklemi çözülerek kanal tabanındaki pürüzlülük ile sürükleme (drag) kuvveti arasında bir ilişki kurulmuştur. Boyutsuz parametreler, boyutsuz sürükleme etkisi ve boyutsuz pürüzlülük etkisi, kullanılarak pürüz yüksekliğinin hidrolik sıçramaya yaptığı etki gözlemlenmiştir. Bu çalışmada ayrıca hidrolik sıçramalar sırasında ortaya çıkan bir diğer önemli fiziksel fenomen olan sıçrama uzunluğu da bir model geliştirilerek eşlenik derinlikler ve menba akış hızı cinsinden yazılmış ve Dikdörtgen kesitlerde sıçrama uzunluğunu tahmin etmek için geliştirilmiştir. Geliştirilen bu denklem farklı pürüzlülük katsayısına sahip olan ortamlar için test edilmiş ve hidrolik sıçrama uzunluğu Dikdörtgen kesitler için modellenmiştir. Anahtar Kelimeler: Hidrolik Sıçrama, pürüzlü yatak, dikdörtgen kanal, sürükleme kuvveti, sıçrama uzunluğu.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2014. Supervisor: Assoc. Prof. Dr. Umut Türker.
Keywords: Civil Engineering; Hydraulic Engineering; Water Power; Hydraulics - Water, Flow of; Hydraulic jump; roughened bed; rectangular channel; drag force; roller length